NOISE MAPPING OF THE UNIVERSITY OF TECHNOLOGY - Abduljabbar Ibrahim, Shatha (Journal of Engineering and Sustainable Development, 2016)
This study aimed to determine noise sources and levels on the campus of the University of Technology, Baghdad, Iraq, using SounPlan7.2 software for noise mapping for different situations. Models were used to investigate the impact of different situations on on-campus development, including constructing new buildings and parking lots, and removal of noise protection walls. Noise mapping for these modeled situations showed potential variations of 10dB(A) in noise levels. The main noise sources on the campus are electrical generators, traffic roads, parking lots, and workshops with open doors which emitted high noise levels exceeding 85dB(A). According to the World Health Organization (WHO), when noise levels exceed 55dB(A), the campus noise environment can be classified as an unpleasant, annoying, and uncomfortable environment.